Impaired Sensitivity to Thyroid Hormones Is Associated with Hyperuricemia, Obesity, and Cardiovascular Disease Risk in Subjects with Subclinical Hypothyroidism - Sun, Ying; Teng, Di; Zhao, Lei; Shi, Xiaoguang; Li, Yongze; Shan, Zhongyan; Teng, Weiping (Thyroid (New York, N.Y.), 2022)
Subclinical hypothyroidism (SCH) is associated with an increased risk of metabolic disorders and cardiovascular events. There is a delicate interplay between thyroid hormones and thyrotropin (TSH) and metabolic homeostasis. However, the association between thyroid hormone sensitivity and metabolic indices has not been elucidated in SCH. We enrolled 11,109 participants with SCH. All participants had a TSH level >4.2 mIU/L and normal free thyroxine (fT4; 12.0-22.0 pmol/L). Metabolic indices (body mass index [BMI], blood pressure, serum lipid, serum uric acid [sUA], plasma glucose and glycosylated hemoglobin [HbA1 ]) were measured. The thyroid hormone sensitivity indices that include thyroid feedback quantile-based index (TFQI), TSH index (TSHI), and thyrotroph thyroxine resistance index (TT4RI) were calculated based on fT4 and TSH. Higher TFQI quartiles indicated lower thyroid hormone sensitivity. The relationship between thyroid hormone sensitivity indices and metabolic indices and cardiovascular disease (CVD) risk were calculated. Participants with decreased central sensitivity to thyroid hormone had lower BMI and higher sUA levels. The odds ratio of the fourth versus the first quartile of TFQI was 0.85 [confidence interval, CI: 0.73-0.96] for obesity, 1.64 [CI: 1.37-1.92] for hyperuricemia (HUA), and 12.22 [CI: 5.32-28.07] for 10-year risk distribution for CVD >20%. Further adjustment for BMI when analyzing HbA1 , HUA, and CVD risk generated similar results. TSHI and TT4RI also yielded similar results. Impaired sensitivity to thyroid hormone in SCH is associated with higher risk of HUA and CVD and lower risk of obesity. These findings are potentially useful for understanding the interaction between thyroid hormone sensitivity and metabolic diseases in SCH.